Methyl Jasmonate Spray Enhances Antioxidant Defense and Preserves Postharvest Quality of Marian Plum (Bouea macrophylla Griffith) During Shelf Life - Supapvanich, Suriyan; Li, Da; Techavuthiporn, Chairat; Suo, Xiaoyu; Youryon, Pannipa; Promyou, Surassawadee; Sinthusamran, Sirima (My University, 2026)
Marian plum (Bouea macrophylla Griff.), an exotic fruit with high commercial potential, has received limited attention in postharvest research. This study evaluated the effects of postharvest methyl jasmonate (MeJA) spray application on the maintenance of physicochemical quality of Marian plums during shelf-life storage under room-temperature (26 ± 1 °C and 70–75% relative humidity) for 12 days. Fruits were treated with MeJA at concentrations of 0 (CK), 0.01, 0.1, and 1 mM. MeJA application did not significantly influence skin colour development and weight loss throughout storage. However, fruit treated with 1 mM MeJA showed reduced visual decay compared with lower concentrations and the CK. Treatments with 0.1 and 1 mM MeJA moderated changes in total soluble solids and titratable acidity, resulting in a higher BrimA index relative to the CK and 0.01 mM treatment. In addition, higher MeJA concentrations delayed fruit softening by slowing insoluble pectin degradation and soluble pectin accumulation during storage. MeJA treatments at 0.1 and 1 mM mitigated oxidative stress by lowering malondialdehyde and lipoxygenase activity, while enhancing antioxidant capacity, total phenolics, and the activities of catalase and ascorbate peroxidase. Pearson’s correlation and principal component analyses confirmed that 0.1 and 1 mM MeJA delayed fruit deterioration by improving antioxidant capacity and preserving texture during shelf life. Overall, these findings suggest that postharvest MeJA application, particularly at 0.1–1 mM, represents a promising and potentially sustainable strategy for extending shelf life and improving the marketability of Marian plum under room-temperature storage.
Keywords: Non-climacteric fruits; Oxidative responses; Physicochemical quality; Plant regulator